The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0084716
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Small Fiber Abnormalities in the Neuropathic Postural Tachycardia Syndrome

Abstract: ObjectiveTo define the neuropathology, clinical phenotype, autonomic physiology and differentiating features in individuals with neuropathic and non-neuropathic postural tachycardia syndrome (POTS).MethodsTwenty-four subjects with POTS and 10 healthy control subjects had skin biopsy analysis of intra-epidermal nerve fiber density (IENFD), quantitative sensory testing (QST) and autonomic testing. Subjects completed quality of life, fatigue and disability questionnaires. Subjects were divided into neuropathic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 48 publications
6
72
0
Order By: Relevance
“…Nevertheless, most of the nerve fiber density values considered abnormal in our study were only slightly below the normal range. Results of a recent study on a smaller group of POTS patients demonstrated that about half (9 of 20) had mildly reduced IENF, which is in line with the results obtained from our larger cohort.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, most of the nerve fiber density values considered abnormal in our study were only slightly below the normal range. Results of a recent study on a smaller group of POTS patients demonstrated that about half (9 of 20) had mildly reduced IENF, which is in line with the results obtained from our larger cohort.…”
Section: Discussionsupporting
confidence: 91%
“…Gibbons and Freeman [25] defined neuropathic POTS as a reduced intra-epidermal nerve fiber density through skin biopsies with impaired sensory or sudomotor function. It is noteworthy that there is not concordance between the different markers of autonomic neuropathy (abnormal skin biopsies, sudomotor testing or quantitative sensory analyses) in the same patient.…”
Section: Resultsmentioning
confidence: 99%
“…Norepinephrine spillover is not a practical clinical test. A thermoregulatory sweat test or a Quantitative Sudomotor Axon Reflex Test (QSART), quantitative sensory testing, or a skin biopsy can also be used to determine whether an autonomic neuropathy exists [44;25]. …”
Section: Pathophysiology Of Potsmentioning
confidence: 99%